Evaluation of VITEK matrix‐assisted laser desorption ionization–time of flight mass spectrometry for identification of anaerobes. (July 2016) - Xiao, Zheng; Luo, Yanping; Ye, Liyan; Wang, Rui; Zhang, Ying; Zhao, Qiang; Guo, Ling; Ma, Yanning; Cui, Shenghui
ABSTRACT: Rapid and adequate identification of anaerobic bacterial species still presents a challenge for most diagnostic laboratories, hindering the selection of appropriate therapy. In this study, the identification capacity of 16S rRNA sequence analysis, VITEK 2 (BioMérieux, Lyon, France) compact analysis and VITEK MS‐mediated identification for anaerobic bacterial species was compared. Eighty‐five anaerobic bacterial isolates from 11 provinces in China belonging to 14 genera were identified by these three methods. Differences in identification between these three methods were compared. Consistent identification results were obtained for 54 (54/85, 63.5%) isolates by all three methods, the most discordant results being concentrated in Clostridium XI ( n = 8) and Bacteroides fragilis ( n = 9) clusters. Using the VITEK MS system, 74 (74/90, 82.2%) isolates were identified as single species consistent with 16S rRNA sequence analysis, which was significantly better than the results obtained with VITEK 2 Compact ( P < 0.01). Misidentifications by the Vitek 2 Compact and Vitek MS systems were mainly observed in the Clostridium XI ( n = 8)and B. fragilis clusters ( n = 9). VITEK MS identified anaerobic bacteria even after they had been exposed to oxygen for a week. Identification by the Vitek MS system was more consistent with 16S rRNA sequence analysis than identification by Vitek 2 Compact. Continuous expansion of the VITEK MS database with rare described anaerobic species is warranted to improve both the efficiency and accuracy of VITEK MS identification in routine diagnostic microbiology.